A new cave-dwelling species of Lagynochthonius (Arachnida: Pseudoscorpiones: Chthoniidae) from Yunnan Province, China - Li, Yun-Chun; Liu, Huai; Shi, Ai-Min (Zootaxa, 2019)
A new pseudoscorpion, Lagynochthonius bailongtanensis sp. nov., is described and illustrated from specimens collected in a cave in Luoping County, Yunnan Province, China. This species is notable in being strongly troglomorphic. A new identification key is provided to all known Chinese representatives of the genus Lagynochthonius.